Persebaran Ikan di Kawasan Tahura Ngurah Rai, Bali - Kamajayanti, Ni Putu Astri; Pertami, Nyoman Dati; Ulinuha, Devi; Pratama, Putu Satya (Current Trends in Aquatic Science; Vol 7 No 1 (2024), 2024)
The diversity of fish species in aquatic estuarine is influenced by the distribution of fish. The pattern distribution of fish in the Ngurah Rai forest park area has never been done, therefore this research was conducted from July to December 2022 to determine distribution of fish which is expected to be used as initial information on ecosystem conditions in the Ngurah Rai forest park area. Fish sampling were carried out every month. The sampling method was carried out using experimental gill nets and traps twice in the morning (tide) and during the day (ebb). The results showed that the total number of fish found around the Ngurah Rai forest park area was 478 individuals with 12 orders, 17 families, and 23 fish species. The most common fish species found in July is Ambasis macracanthus (Seriding). Furthermore, sequentially the fish species are Fibramia lateralis (Serinding), Aurigequula fasciata (Cotek), Ophiocara ophicephalus (Bedul), and Plotosus canius (Nine). Specifically in November, no dominant species was found.